Truth or Trend? The Complex Reality of Workplace Mental Health Research Amidst Diagnostic Ambiguity and Misconduct Risks - Pranata Priyo Prakoso; Ray Wagiu Basrowi (ILUNI MKK FKUI and PRODI MKK FKUI, 2024)
Background: Awareness of mental health grew during the COVID-19 pandemic, driven further by globalization, social media access, and the younger generation increasingly entering the workforce.1 These factors contributed to future increasing number of research on this topic. Due to the sensitive nature of mental health and other factors like the involvement of workplace stakeholders, publishing pressure, and incentives, workplace mental health research is susceptible to biases or misconduct. Objective: This review aims to describe potential mechanism of misconduct in workplace mental health research and how important reader’s role to interpret such studies Methods: A narrative review is conducted to highlight studies on scientific misconduct in mental health research in workplace using PubMed, Google Scholar, and Retraction Watch. Six studies in psychiatric, mental health, and general scientific misconduct are used since scarcity on explicitly conducted study on the topic. Results: Key findings include the possibility of positive reporting bias, subjectivity in mental health assessments raise questions about unethical research procedures, sample representation and research integrity, the use of cross-sectional study designs might distort causal links, and publication pressures may lead to data modification or fabrication. To address these concerns, readers must be involved in critically examining and questioning research integrity.Conclusion: These findings highlight the importance of transparency, the risks of publication bias, and the pervasive influence of publishability pressures. Notably, diagnostic uncertainty, the frequency of subjective assessments, and cross-sectional study methods all complicate the interpretation of findings in this area.